Eco-friendly synthesis of copper oxide nanomaterial by using Musa paradisiaca leaves extract and their slow pyrolysis or catalytic reduction activities - Rida Khalid; Muhammad Imran Din; Zaib Hussain (Next Nanotechnology)
Copper oxide nanoparticles (CuO NPs) have been prepared via sol-gel synthetic approach using aqueous leaves extract of Musa paradisiacal and copper chloride dehydrate salt. UV visible spectroscopy showed maximum peak for CuO NPs at 535 nm. Additionally, the SEM XRD techniques confirmed spherical shape of CuO NPs with average size of 15 nm. Nitro compounds have been carefully chosen as a tested contaminant to study performance of CuO NPs. Catalytic reduction of nitro compounds was investigated under different temperatures to evaluate thermodynamic studies. According to the results, catalytic reduction of nitro compounds obeys Langmuir–Hinshelwood mechanism. The value of apparent rate constant shows a linear trend with catalyst concentration. The catalytic pyrolysis of corncob biomass in the presence of CuO NPs showed more bio-oil (46.13 %) yield as compared to ZSM-5 (40.07 %) and without catalyst (37.09 %) reactions. The data also confirmed that CuO NPs showed excellent performance as a micro-reactor for catalytic degradation of nitro compounds and catalytic pyrolysis. The CuO NPs have been isolated and reused in 5 consecutive cycles with good and reproducible excellent performance.